2018
DOI: 10.1140/epjc/s10052-018-5878-x
|View full text |Cite
|
Sign up to set email alerts
|

On the initial conditions of scalar and tensor fluctuations in $$f(R,\phi )$$ f ( R , ϕ ) gravity

Abstract: We have considered the perturbation equations governing the growth of fluctuations during inflation in generalized scalar tensor theory f (R, φ). We have found that the scalar metric perturbations at very early times are negligible compared to the scalar field perturbation, just like general relativity. At sufficiently early times, when the physical momentum of perturbation mode, q/a is much larger than the Hubble parameter H , i.e. q/a H , we have obtained the metric and scalar field perturbation in the form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…In f (R) gravity, choosing the gauge condition δF = 0, as a specific choice, effectively removes some degrees of freedom and the Mukhanov-Sasaki equation is easily obtained. Even for a general f (R, f) gravity, one can introduce a new gauge by which the generalized Mukhanovâ-Sasaki equation is derived straightforwardly [24]. 6 Here we do not specify the gauge.…”
Section: Vacuum Ambiguity In F (R) Inflationary Cosmologymentioning
confidence: 99%
“…In f (R) gravity, choosing the gauge condition δF = 0, as a specific choice, effectively removes some degrees of freedom and the Mukhanov-Sasaki equation is easily obtained. Even for a general f (R, f) gravity, one can introduce a new gauge by which the generalized Mukhanovâ-Sasaki equation is derived straightforwardly [24]. 6 Here we do not specify the gauge.…”
Section: Vacuum Ambiguity In F (R) Inflationary Cosmologymentioning
confidence: 99%
“…where h is another constant which can be obtained by the initial condition of metric perturbation in the Jordan frame at the time of horizon crossing [21]. By using equation (29), it is straightforward to see that δF 2F = κ 2 6 δξ (50)…”
Section: Scalar Perturbationsmentioning
confidence: 99%
“…and the Fourier transforms of the metric and scalar perturbations, δφ k , satisfy in the following equations [21] 3…”
Section: Scalar Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their investigation showed that this theory can support a viable inflationary model that includes a well-functioning exit strategy. Numerous cosmological issues are examined by researchers in this theory [18]. This theory has further been modified by including the kinetic term in the action, called f (R, j, χ) theory [19].…”
Section: Introductionmentioning
confidence: 99%